Toxicology and risk assessment : a comprehensive introduction. - Greim, Helmut, ....-; Snyder, Robert, 1935- (Chichester : Wiley, 2008)
This new book, written by two outstanding scientists in the field, describes the basic principles of toxic mechanisms and organ toxicity, providing detailed information on specific mechanisms or chemicals for exemplification. The goal is to provide sufficient information that the reader becomes familiar with the basic concepts in toxicology to enable him or her to understand the basic principles in toxicology and to evaluate the risks at given exposures. With this basic understanding the reader also will be able to critically evaluate the available information on a chemical and to identify data gaps. In addition to the introductory chapters the book will offer the following systematic information, presented in six special sections: Principles in Toxicology Organ Toxicology Methods in Toxicology Risk Assessment Risk Management Toxicity of Chemicals Fulfilling a demand for such a book, this will be a welcomed introductory text for students and non-experts alike to focus on and understand the principles of hazard identification and risk assessment of toxicants. Relevant to all those studying toxicology, biochemistry, biology, medicine and chemistry, as well as toxicologists in hospitals, universities and in industry.